Production of L-asparaginase of pharmaceutical nterest from yeasts isolated from the Antarctic continent - Moguel, Ignacio Sánchez (2018)
The L-asparaginase (ASNase) obtained from yeasts species has been poorly studied and a new yeast ASNase could be an alternative to minimize the side effect in the treatment of lymphoblastic leukemia. The Antarctic ecosystems have a great potential to obtain novel enzymes produced from psychrophilic and psychrotolerant microorganisms. Yeasts isolated from samples collected in the Antarctic Peninsula by the PROANTAR expedition team were tested for the production of ASNase and L-glutaminase (GLNase). From this screening, the strain Leucosporidium scottii L115 presented the highest ASNase activity (6.24 U g-1 of dried cell weight (dcw)) with a combination of low GLNase activity (0.41 U g-1 dcw). The ASNase belonging to L. scottii L115 (LsASNase) was purified 227 fold with a specific activity of 137.01 U mg-1 at 37 ºC, and with 0.93 U mg-1 for GLNase. Moreover, the maximum activity was observed at pH 7.5 at 55 ºC. The enzyme is a multimer presenting a single band of 54.5 kDa of molecular weight in reduced conditions and 462 kDa by size exclusion chromatography. The LsASNase is a glycosylated enzyme that presented a band lower at 25 kDa when was treated with PGNase F. The enzymatic kinetic reveals an allosteric regulation of the enzyme and the kinetic parameters were determined at 37º C, pH 7.0 as K0.5 = 233 µM, kcat = 54.7 s-1 and nH = 1.52 demonstrating a positive cooperativity by the enzyme and the substrate. The ASNase production by L. scottii L115 was improved by applying DoE for the culture medium development. The PB and CDD designs were used to optimize the ASNase production providing the nutrient values of 6.15 g L-1 of proline, 28.34 g L-1 sucrose, and 15.61 g L-1 of glycerol for a maximal production. The synthetic medium containing the optimized quantities was added with the salts: KCl, 0.52 g L-1; MgSO4.7H2O, 0.52 g L-1; CuNO3.3H2O, 0.001 g L-1; ZnSO4.7H2O, 0.001 g L-1; FeSO4.7H2O, 0.001 g L-1.The optimized medium produces a 23.75 ULh-1 of ASNase in shake flask culture. Furthermore, L. scottii is characterized as an oleaginous yeast that accumulates lipids with a suitable fatty acid profile. The production of ASNase and lipids were scaled up in the 1 L bioreactor to evaluate the initial cell concentration, carbon source, and oxygen transfer rate (kLa).The experiments were performed at 15ºC in the bioreactor BIOSTAT®Q plus (Sartorius Stedim, Germany) in batch mode, using 0.5 L of the optimized medium culture in phosphate buffer 50 mM pH 7.0. The initial cell concentration was evaluated at 1%, 3%, and 5% (v/v). Sucrose and glycerol were tested alone to examine if the combination of both is mandatory to produce ASNase. All these assays were carried in duplicate. The kLa was assessed through a CCD design in the range of 1.42 - 123.0 h-1. The performance in bioreactor showed the productivity of 36.95 ULh-1of ASNase under the optimized conditions (growth temperature 15º C, X0: 5 g L-1, pH 7.0, 48 h, kLa 89-92 h-1). The cultivation of L. scottii L115 at 15ºC in sucrose and glycerol as carbon sources generate an interesting lipid profile, where it presents monounsaturated and polyunsaturated lipids.